Effects of nutritional factors on growth of lactobacillus fermentum mixed with saccharomyces cerevisiae in alcoholic fermentation - De Oliva-Neto, Pedro [UNESP]; Yokoya, Fumio (My University, 1997)
The growth of Lactobacillus fermentum was studied in mixed culture with Saccharomyces cerevisiae during alcoholic fermentation of high test molasses (HTM).Yeast extract or a group of 17 amino acids caused a strong and fast decrease in yeast viability due to the strong increase of acidity produced by bacteria. Pure culture of Lactobacillus fermentum in dry sugar cane broth confirmed amino acids as the main nutrients needed to stimulate the growth of bacterial contaminant during alcoholic fermentation. The absence of L. fermentum growth was obtained when leucine, isoleucine or valine were not added to the medium. Phenylalanine, alanine, glutamic acid, cystine, proline, histidine, arginine, threonine, tryptophane, serine and methionine inhibited the bacterial growth at least in one of the cultures of L. fermentum tested.
Keywords: Amino acids; Growth; Lactobacillus fermentum; Mixed culture; Saccharomyces cerevisiae; Stimulation